Razumevanje nacionalne in evropske identiteta - primer Češke republike - Cabada, Ladislav (Teorija in praksa, 2000)
The process of connecting European countries and establishing unified European state may take many different ways. European Union was chosen to be the basis for forming federal Europe. It is transferring slowly from an economic organisation to organisation with state attributes. The appearance of European state depends on whether the European Union succeeds in implementing basic presumptions of federalisation - forming European identity and respecting national and regional identities. The process of forming common European identity will be a long process and its success depends on long-term economic and political prosperity of European Union or state. Economic recession would mean renouncement of European identity and return of European citizens to national identities. Czech republic represents an example of a small country, being aware of importance of accession to European Union. However, their political elite is not able to agree upon the political priorities. Pro-european politics thus stagnates and defenders of European politics are limited due to a great coalition of 'Euro-sceptics'. Despite the real politics, a majority of Czech public supports accession to European Union.
Keywords: European Union; Evropska unija; narodna identiteta; evropska identiteta; Czech Republic; Češka; integracijski procesi